(untitled) (Journal of Misan Researches, 2020)
The research aims to highlight the reality of secondary education in the province of Maysan during the period 1968_1979, and to highlight it through the policy of the government followed in that period. The first section deals with the reality of education in Iraq during the research period and its impact on the province. The second section deals with the reality of education in Maysan by studying a model of schools in the province. The conclusion showed the most important findings and conclusions reached by the researcher.